Urgensi Analisis Strategi Dalam Pengembangan Rumah Sakit RSUD X (Studi Kasus): Urgency of Strategy Analysis in the Development of X Regional Public Hospital (A Case Study) - Reny Hasanah (JURNAL TERAS KESEHATAN, 2018)
This research to discribe the urgency of strategic analysis for a leaderand hospital management as basic hospital development regardingphysical The X Hospital development, plan wich one of part west Javadistric Hospital.Research methode applied in descriptive qualitative united and quatitative with 11 (eleven) interviewer population hospital developmentteam and 4 (four) sources sample. Primary and secundary data used.Processing data applied Fred R David and General Elctric conseptThe result shown base on EFE and IFE analysis which map on The XHospital SWOT in third quadran with implication The X Hospital needto do a restructure consolidation. Chosen alternative strategy from IEmatrix,The X Hospital in the first cell meaning Growth and build withimplication product and market development strategy appropiate withTOWS analysis result. This strategic option strenghten with GE strategy